Cold atmospheric plasma improves antifungal responsiveness of Aspergillus flavus and Fusarium keratoplasticum conidia and mycelia - Darby M. Roberts; Jonathan E. Thomas; Jacklyn H. Salmon; Marc A. Cubeta; Katharina Stapelmann; Brian C. Gilger (PLoS ONE, 2025)
The purpose of this study is to evaluate sublethal cold atmospheric plasma (CAP) treatment of filamentous fungal pathogen susceptibility to commonly used antifungal drugs in vitro. Response to CAP in combination with voriconazole, fluconazole, amphotericin B, and caspofungin was evaluated in Aspergillus flavus and Fusarium keratoplasticum conidia and mycelium; conidial response to fluconazole was also assessed in three strains of F. falciforme. Conidial susceptibility to antifungal drugs alone or in combination with CAP was assessed using a modified CLSI broth microdilution assay with MIC determination and colony-forming unit (CFU) enumeration. Mycelial viability and biofilm thickness changes in response to antifungal drugs alone or in combination with CAP were assessed over 24 hours post treatment. CAP enhanced antifungal drug efficacy against all fungal species, though effects differed by drug and growth form. CAP enhanced antifungal drug susceptibility in conidia, with the strongest effect observed for F. keratoplasticum conidia, where caspofungin MIC decreased fourfold (from 16 to 4−8 μg/mL) and sensitivity to fluconazole, which exerted no effect in absence of CAP, was restored when combined with sublethal CAP treatment. In A. flavus, CAP lowered the MIC of voriconazole (from 0.25 to 0.06–0.125 μg/mL) but increased the MIC of amphotericin B (from 4 to >4 μg/mL), despite reductions in viable cell counts. Differential responses to CAP and fluconazole were observed across three strains of F. falciforme, suggesting variability in CAP response. In treated biofilms, CAP alone initially reduced mycelial viability and biofilm thickness, but partial recovery of the fungus was observed over time in most cases. When combined with antifungal drugs, CAP significantly enhanced reduction of mycelial viability and thickness beyond antifungal treatment alone. In F. keratoplasticum biofilms, the combination of CAP and antifungal drugs produced sustained reductions in mycelial viability and biofilm thickness, whereas A. flavus biofilms were more resistant to CAP treatment and exhibited consistent recovery after 24 hours.